Peri-operative allogeneic blood transfusion does not adversely affect oncological outcomes after radical cystectomy for urinary bladder cancer: a propensity score-weighted European multicentre study - Vetterlein, Malte Wolfram; Nuhn, Philipp (BJU international, 2018)
Objectives To evaluate the effect of peri-operative blood transfusion (PBT) on recurrence-free survival, overall survival, cancer-specific mortality and other-cause mortality in patients undergoing radical cystectomy (RC), using a contemporary European multicentre cohort. Patients and Methods The Prospective Multicentre Radical Cystectomy Series (PROMETRICS) includes data on 679 patients who underwent RC at 18 European tertiary care centres in 2011. The association between PBT and oncological survival outcomes was assessed using Kaplan-Meier, Cox regression and competing-risks analyses. Imbalances in clinicopathological features between patients receiving PBT vs those not receiving PBT were mitigated using conventional multivariable adjusting as well as inverse probability of treatment weighting (IPTW). Results Overall, 611 patients had complete information on PBT, and 315 (51.6%) received PBT. The two groups (PBT vs no PBT) differed significantly with respect to most clinicopathological features, including peri-operative blood loss: median (interquartile range [IQR]) 1000 (600-1500) mL vs 500 (400-800) mL (P < 0.001). Independent predictors of receipt of PBT in multivariable logistic regression analysis were female gender (odds ratio [OR] 5.05, 95% confidence interval [CI] 2.62-9.71; P < 0.001), body mass index (OR 0.91, 95% CI 0.87-0.95; P < 0.001), type of urinary diversion (OR 0.38, 95% CI 0.18-0.82; P = 0.013), blood loss (OR 1.32, 95% CI 1.23-1.40; P < 0.001), neoadjuvant chemotherapy (OR 2.62, 95% CI 1.37-5.00; P = 0.004), and ≥pT3 tumours (OR 1.59, 95% CI 1.02-2.48; P = 0.041). In 531 patients with complete data on survival outcomes, unweighted and unadjusted survival analyses showed worse overall survival, cancer-specific mortality and other-cause mortality rates for patients receiving PBT(P < 0.001, P = 0.017 and P = 0.001, respectively). After IPTW adjustment, those differences no longer held true. PBT was not associated with recurrence-free survival (hazard ratio [HR] 0.92, 95% CI 0.53-1.58; P = 0.8), overall survival (HR 1.06, 95% CI 0.55-2.05; P = 0.9), cancer-specific mortality (sub-HR 1.09, 95% CI 0.62-1.92; P = 0.8) and other-cause mortality (sub-HR 1.00, 95% CI 0.26-3.85; P > 0.9) in IPTW-adjusted Cox regression and competing-risks analyses. The same held true in conventional multivariable Cox and competing-risks analyses, where PBT could not be confirmed as a predictor of any given endpoint (all P values >0.05). Conclusion The present results did not show an adverse effect of PBT on oncological outcomes after adjusting for baseline differences in patient characteristics.